Patterns of Change in Telomere Length over the First Three Years of Life in Healthy Children - Bosquet Enlow, Michelle (Psychoneuroendocrinology, 2020)
There is growing interest in the use of telomere length as a biomarker of health and a predictor of later morbidity and mortality. However, little is known about developmentally expected telomere erosion over the first years of life. This gap hinders our ability to interpret the meaning of relative telomere length and rate of attrition in relation to risk factors and health outcomes. The overall goal of this study was to examine the rate of relative telomere length attrition in a large, normative sample of healthy children (N=630) followed from infancy to three years of age. A secondary goal was to explore associations between sociodemographic characteristics and telomere erosion over this time period. Relative telomere length was assessed from DNA in saliva samples collected in infancy (M =8.6 months), age 2 years (M =25.2 months), and age 3 years (M=38.3 months). In the sample as a whole, relative telomere length decreased from infancy to 2 years but remained stable from 2 years to 3 years. Notably, increases in relative telomere length were observed in 29% of children between infancy and 2 years of age and in 46% of children between 2 and 3 years of age; 62% of children showed both increases and decreases in relative telomere length across the study period. Females showed longer relative telomere length than males, regardless of timepoint. There was some evidence that parental age and family finances were associated with changes in child relative telomere length across time. Overall, the findings suggest that telomere length attrition is not uniform across the early years of life, with the most rapid attrition occurring during the first two years, and that increases as well as decreases in telomere length during this period are commonly observed.